Library Anxiety Among Students toward the Digital Library Services at Padang State University - Viola Alvina Santika; Marlini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The expansion of digital library services has improved students’ access to academic information resources; however, difficulties encountered when using these services may contribute to library anxiety and impede effective information seeking. This study aimed to determine the level of library anxiety experienced by students when using digital library services at Padang State University Library. A quantitative descriptive design was employed, with a population of 8,282 active students and a purposively selected sample of 99 participants. Data were collected through observation and questionnaires and analyzed using descriptive statistics based on a four-point Likert scale to calculate mean and grand mean scores. The findings revealed that students’ library anxiety when using digital library services was classified as slightly anxious, with a mean score of 2.46. This result indicates that, although students generally experience a relatively low level of anxiety, barriers to using digital library services remain and may affect their ability to retrieve academic information effectively. The study concludes that digital library services should be strengthened through more user-friendly information retrieval systems, librarian-assisted training, and enhanced information literacy programs. These findings extend research based on the Polish Library Anxiety Scale within the context of digital library services and provide practical implications for university libraries seeking to reduce students’ anxiety and improve their digital information-seeking experiences.